Traffic and environmental street network modelling: Belgrade case study - Jović, Jadranka; Đorić, Vladimir (Transport, 2010)
The paper presents a procedure for modelling transport demand and analyses effects caused by changes in the characteristics of street network exploitation. Based on the effects of the measures predominantly connected with speed restrictions on characteristic sections, the Scenarios resulting in reduced congestion during peak hour and a decrease in harmful effects of traffic were selected. A rough effectivity analysis of transport vehicle kilometres travelled and travel time on the network was carried out. Transportation modeling is the most efficient way to analyze the effects of traffic solutions. Once established, transport model brings only benefits in future projects. Speed reduction strategy was easily simulated using the transportation modeling procedure. Other sustainable transport and mobility management strategies considering sustainable transportation could also be simulated.First published online: 24 jun 2011